The Legacy of Sir Syed Ahmad Khan in the Field of Education - Ali, Fayyaz; Shahzada, Gulap; Faqir, Khan (Mediterranean Journal of Social Sciences, 2011)
It is beyond any doubt that education has been the dire need of any society. Education is a life-long process. It continues fromthe cradle to the grave. It equips people with knowledge and skills to enable them to live a prosperous and happy life. Education serves assupra structure of a country. The development of country depends upon the standard and quality of education in the country. Education isa mean through which a man knows himself and his position and duties in this world. It helps individual in self-realization and is aprocess of exploring of individual’s potentiality and tries to enable the individual using his power in positive manner (Khalid, 1998). Thearrival of Syed Ahmad Khan on the India educational scene is perhaps the most outstanding event in the 19th century in the history ofMuslim education. This paper will analyze the views, educational philosophy and contribution of Sir Syed in the field of education and theout put of Aligarh Movement initiated by Sir Syed Ahmad Khan.